Tren Pendekatan Pembelajaran Matematika di Sekolah Dasar Periode 2020-2025 - Nurhasanah Nurhasanah; Budiyono Budiyono; Nuni Widiarti; Arif Widiyatmoko (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Mathematics education in elementary schools (SD) plays a crucial role in developing students' cognitive abilities, critical thinking, and numeracy literacy. However, various reports indicate that Indonesian students' mathematics learning outcomes remain relatively low, including findings from the Programme for International Student Assessment (PISA) 2023, which placed the majority of students at a low level of numeracy literacy. This condition indicates the need for learning innovations that align with the spirit of the Independent Curriculum. This article aims to map the implementation trends and effectiveness of four mathematics learning approaches in elementary schools during the 2020–2025 period: Realistic Mathematics Learning (PMR), Culturally Responsive Teaching (CRT), differentiated learning, and deep learning. This study uses the Systematic Literature Review (SLR) method with PRISMA guidelines through article searches on Google Scholar and analyzed descriptively qualitatively. The results of the study indicate that all four approaches contribute positively to improving learning outcomes, student engagement, and critical and creative thinking skills. Although no approach is absolutely superior, integration between approaches has the potential to produce more contextual, adaptive, and sustainable mathematics learning in elementary schools.